Colored travelers : mobility and the fight for citizenship before the Civil War - Pryor, Elizabeth Stordeur (John Hope Franklin series in African American history and culture., 2016)
"Americans have long regarded the freedom of travel a central tenet of citizenship. Yet, in the United States, freedom of movement has historically been a right reserved for whites. In this book, Elizabeth Stordeur Pryor shows that African Americans fought obstructions to their mobility over 100 years before Rosa Parks refused to give up her seat on a Montgomery bus. These were "colored travelers," activists who relied on steamships, stagecoaches, and railroads to expand their networks and to fight slavery and racism. This book tells the story of how the basic act of traveling emerged as a front line in the battle for African American equal rights before the Civil War"--